A constitutive model of polyether-ether-ketone (PEEK) - Chen, Fei; Ou, Hengan; Lu, Bin; Long, Hui (Elsevier, 2016)
A modified Johnson–Cook (JC) model was proposed to describe the flow behaviour of polyether-ether-ketone (PEEK) with the consideration of coupled effects of strain, strain rate and temperature. As compared to traditional JC model, the modified one has better ability to predict the flow behaviour at elevated temperature conditions. In particular, the yield stress was found to be inversely proportional to temperature from the predictions of the proposed model.